Item Analysis for Trait Emotional Intelligence Questionnaire Short Form (TEIQue-SF) - Simanjuntak, Maria Jane Tienoviani; Moningka, Clara (Universitas Mercu Buana Jakarta, 2025)
In this study, the researcher analyzed the TEIQue-SF (Trait Emotional Intelligence Questionnaire-Short Form) from Petrides (2009), which consists of fifteen facets of trait emotional intelligence and is measured by thirty items. The questionnaire measures four dimensions: emotionality, sociability, well-being, and self-control. This research involved 339 respondents from Indonesia. Reliability testing was conducted using Cronbach’s Alpha. Discriminant analysis is conducted by examining the item-rest correlation. The results of this study indicate that the TEIQue-SF (Trait Emotional Intelligence Questionnaire-Short Form) is divided into two dimensions. The adaptation into Indonesia allows for cross-cultural validation studies and expands Indonesian contributions to global EI research. This research also facilitates more accurate and meaningful data collection in psychological research related to the trait of emotional intelligence.